Teaching Pragmatic Competence: Challenges and Strategies for Second Language Learners in the Digital Age: https://doi.org/10.5281/zenodo.17046754 - Muhammad Shaffaqat; Marta Martín de Vidales Martín; Wali Hussain (`, 2025)
The digital age has permanently reshaped the landscape of the human society, thus necessitating a radical realignment of the objectives upon which the pedagogy of the second Language (L2) is based. Although grammatical accuracy continues to hold the top rank, it has become more and more true that the achievement of legitimate communicative competence is directly dependent upon the pragmatic skill of an interlocutor the ability to mobilize language in a way that is in line with the existing social and cultural environment. This article posits that online spaces, which include social media, instant messaging, electronic mail and videoconferencing, have created unique practical rules and challenges that are that are currently being faced by the traditional, analogue-based ways of teaching languages that are ill equipped to handle. Therefore, L2 learners face considerable challenges, including the ability to infer affective tone when devoid of paralinguistic messages, the fluidity of the register across digital genres, the ability to interpret culturally specific jokes and memes, and the possibility of carrying out a speech act based on textual activity. This conceptual manuscript is based on an integrative theoretical schema that combines the Sociocultural Theory, Language Socialization, and Multimodality to synthesize the modern body of scholarship with the necessary respect to explain these issues in an exhaustive manner. As a remedy, it introduces a very strong pedagogical model that aims at entrenching digital pragmatics in L2 curriculum. Multi-strategic approach recommends metadata discourse, critical digital literacy and task-based language teaching that includes authentic digital goals, and telecollaborative projects. The article ends by claiming that making learners with strategic competence to analyses and engage in digital discourses is not a side objective but a major requirement of modern language teaching and hence they can turn into competent and pragmatic communicators in a modern interrelated world. Keywords: Pragmatic Competence, Digital Literacy, Computer-Mediated Communication (CMC), Second Language Pedagogy, Task-Based Language Teaching, Telecollaboration